NETWORK AUTOMATION USING PYTHON LIBRARY AND ANSIBLE FOR CISCO ROUTER MANAGEMENT - Wijaya, Jonathan
Nowadays, the development of the internet is very fast and covers the whole world. The rapid and wide development of the internet has caused an increase in the number of active network devices. These network devices come from a number of different vendors, and each vendor has its own configuration method. This certainly makes it difficult for network engineers to configure the device. The number of devices that need to be configured also causes increased resources needed, especially money and time. This final project is based on the problem. In this final project, a network automation system will be created which aims to facilitate configuration of devices with different vendors and in large quantities. This network automation system is expected to be more time efficient compared to direct configuration via the CLI on network devices. The process of forming this system uses the literature study method, which is studying references from journals and the internet, as well as experimental study methods, namely by studying causation by conducting testing. From this method, NAPALM was found as a solution for multi-vendor configuration, and Ansible as a solution for massive device configuration. Both of these tools are combined to create a centralized network automation system. The system that has been created is then tested for performance by looking at the accuracy of the configuration and speed. Testing is done with several scenarios, then one of them will be measured in time to be compared with the manual configuration. The output of this research is expected to be useful for the treasures of science and can be used for further development.